2016
DOI: 10.1111/bph.13522
|View full text |Cite|
|
Sign up to set email alerts
|

Signal transduction pathways activated by insulin‐like peptide 5 at the relaxin family peptide RXFP4 receptor

Abstract: BACKGROUND AND PURPOSEInsulin-like peptide 5 (INSL5) is a two-chain, three-disulfide-bonded peptide of the insulin/relaxin superfamily, uniquely expressed in enteroendocrine L-cells of the colon. It is the cognate ligand of relaxin family peptide RXFP4 receptor that is mainly expressed in the colorectum and enteric nervous system. This study identifies new signalling pathways activated by INSL5 acting on RXFP4 receptors. EXPERIMENTAL APPROACHINSL5/RXFP4 receptor signalling was investigated using AlphaScreen® p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…The sustained cAMP activity seen at RXFP1 and RXFP2 is consistent with the finding that these receptors lack β‐arrestin‐mediated desensitization and show poor internalization in response to ligand stimulation . However, we also saw sustained cAMP inhibition at RXFP3 (particularly in HEK293T cells) and RXFP4, which have been shown to interact with β‐arrestins and internalize after stimulation with their endogenous ligands . Although the original characterization of CAMYEL in RAW 264.7 murine macrophage cells showed that CAMYEL can report substantial and rapid decreases in BRET signal, studies on some GPCRs, including the cannabinoid 1, dopamine D 2 L, and mu‐opioid receptors, have also shown relatively sustained changes in CAMYEL signal over extended periods of time.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The sustained cAMP activity seen at RXFP1 and RXFP2 is consistent with the finding that these receptors lack β‐arrestin‐mediated desensitization and show poor internalization in response to ligand stimulation . However, we also saw sustained cAMP inhibition at RXFP3 (particularly in HEK293T cells) and RXFP4, which have been shown to interact with β‐arrestins and internalize after stimulation with their endogenous ligands . Although the original characterization of CAMYEL in RAW 264.7 murine macrophage cells showed that CAMYEL can report substantial and rapid decreases in BRET signal, studies on some GPCRs, including the cannabinoid 1, dopamine D 2 L, and mu‐opioid receptors, have also shown relatively sustained changes in CAMYEL signal over extended periods of time.…”
Section: Discussionsupporting
confidence: 87%
“…(particularly in HEK293T cells) and RXFP4, which have been shown to interact with β-arrestins and internalize after stimulation with their endogenous ligands. 14,15 Although the original characterization of CAMYEL in RAW 264.7 murine macrophage cells showed that CAMYEL can report substantial and rapid decreases in BRET signal, 20 studies on some GPCRs, including the cannabinoid 1, 40 dopamine D 2 L, 19 and mu-opioid 34 Targeting RXFP receptors with drugs has potential for a range of therapeutic applications (reviewed in 4). Much effort has therefore been put into designing analogues of relaxin family peptides, including agonists and antagonists used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key residues involved in interaction with RXFP4 receptors have been identified and a minimized analogue that is both easier to assemble and potent is now available. The paper by Ang et al , () is one of the few published to date that examines signalling pathways activated by RXFP4 receptors (Figure ). Not only do these receptors inhibit cAMP production but they also activate p38MAPK, ERK1/2, Akt and S6RP.…”
mentioning
confidence: 99%